2015
DOI: 10.1007/s11999-014-4001-3
|View full text |Cite
|
Sign up to set email alerts
|

What Are the Demographic and Radiographic Characteristics of Patients With Symptomatic Extraarticular Femoroacetabular Impingement?

Abstract: Extraarticular FAI is an uncommon source of impingement symptoms. We suspect the diagnosis often is missed, because many of these patients had prior hip surgery before the procedure that diagnosed the extraarticular impingement source. This diagnosis seems more common in younger, female patients. Radiographic and physical examination findings correspond to locations of intraoperative extraarticular impingement. Future studies will need to determine whether surgical treatment of extraarticular impingement patho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 32 publications
0
33
0
2
Order By: Relevance
“…Failure to recognise atypical impingement may contribute to lack of success of the index surgery. There is an increased prevalence of extra articular impingement in young women after hip surgery . In a large series, extra articular impingement was present in 9.5% of cases undergoing revision surgery .…”
Section: Factors Associated With Persistent or Recurrent Symptomsmentioning
confidence: 97%
“…Failure to recognise atypical impingement may contribute to lack of success of the index surgery. There is an increased prevalence of extra articular impingement in young women after hip surgery . In a large series, extra articular impingement was present in 9.5% of cases undergoing revision surgery .…”
Section: Factors Associated With Persistent or Recurrent Symptomsmentioning
confidence: 97%
“…It is thought that isolated extraarticular impingement (excluding isolated subspine impingement) is relatively unprevalent, accounting for only 4% of cases in a database of 1,765 patients treated for FAI. 11 Authors have suggested that several factors should increase the clinical suspicion for extra-articular FAI including lateral or posterior hip pain, limited hip ROM without significant radiographic femoral or acetabular sided deformities, pain reproduced by passive or active hip extension with external rotation, hip pain that is not relieved following intra-articular hip anesthetic injection, and as a cause of persistent pain after prior arthroscopic FAI correction when there is no identifiable residual deformity. 11 One study looked at the demographic and radiographic characteristics of patients with extra-articular FAI and found that these individuals were younger, more frequently female, and with greater preoperative disability based on patient-reported outcome measure (PROM)'s compared with a cohort of patients with intra-articular FAI.…”
Section: Extra-articular Proximal Femoral/pelvic Impingementmentioning
confidence: 99%
“…11 Authors have suggested that several factors should increase the clinical suspicion for extra-articular FAI including lateral or posterior hip pain, limited hip ROM without significant radiographic femoral or acetabular sided deformities, pain reproduced by passive or active hip extension with external rotation, hip pain that is not relieved following intra-articular hip anesthetic injection, and as a cause of persistent pain after prior arthroscopic FAI correction when there is no identifiable residual deformity. 11 One study looked at the demographic and radiographic characteristics of patients with extra-articular FAI and found that these individuals were younger, more frequently female, and with greater preoperative disability based on patient-reported outcome measure (PROM)'s compared with a cohort of patients with intra-articular FAI. 11 This paper subdivides proximal femoropelvic impingement into three subtypes: posterior greater trochanteric-pelvic/ischiofemoral impingement, anterior greater trochanteric pelvic impingement, and lateral/complex greater trochanteric-pelvic impingement.…”
Section: Extra-articular Proximal Femoral/pelvic Impingementmentioning
confidence: 99%
See 1 more Smart Citation
“…This type of impingement is rare, occurring in only 4% of patients with hip pain. 1 The diagnosis can be challenging because extraarticular impingement may coexist with cam or pincer morphology as seen in classical FAI. Extra-articular impingement can be consequential to activities requiring extreme range of motion such as gymnastics or dance 2 but may also be experienced with activities of daily living.…”
Section: Introductionmentioning
confidence: 99%